PROMOTION, PRODUCT QUALITY, MENU DIVERSITY AND PURCHASE DECISIONS FACTORS FOR STREET VENDORS IN THE NEW NORMAL ERA - Handayani, Christina Menuk Sri; Wibowo, Tony Susilo; Laksono, Bayu Rama (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
During the Covid-19 pandemic, Street Vendors (PKL) were devastated, especially with the enactment of PSBB and PPKM in Surabaya, causing their businesses to experience a decline. Along with the decline in the Covid-19 outbreak in Surabaya, supported by a circular letter from the Minister of Trade which stated that street vendors were allowed to operate by complying with the Health Protocol SOPs, street vendors began to rise again and people began to take advantage of them. For this reason, this study aims to determine the factors that influence people's decisions to buy at street vendors in Surabaya in the new normal era whether it is because of promotion, product quality and menu diversity. Quantitative methods are used in this study with a sample of 120 people as respondents and taken randomly. Questionnaires are used to retrieve data that has been systematically compiled containing statements to obtain data on the variables studied. Requirements tests such as instrument tests and classical assumption tests are performed to initiate multiple regression analysis. The test results state that promotion factors, product quality, menu diversity have a positive and significant influence on purchasing decisions at street vendors in Surabaya in the new normal era with significant values of 0.000 each; 0.003 and 0.000.